Study of chemical and thermal properties of kenaf biomass-based polylactic acid (PLA) - Mohd Nasir, Nur Aimi; Anuar, Hazleen; Mel, Maizirwan; Othman, Rashidi; Mohamed, Nurhafizah Seeni; Mohd Ithnin, Ahmad Fitrie; Uyup, Mohd Khairun Anwar (American-Eurasian Network for Scientific Information, 2014)
The development of polylactic acid (PLA) from natural source remains a great challenge. PLA can be produced from its monomer (i.e. lactic acid) via fermentation process. In this study, the production of PLA from kenaf biomass was investigated. It was started with the introduction of kenaf biomass as the renewable source. Since kenaf is a lignocellulosic material, pretreatment process is preferable prior to the fermentation process. Different types of pretreatment methods have been investigated. However, the dilute acid hydrolysis method has been chosen in this project due to its outstanding advantages compared to other processes. After the pretreatment process, kenaf biomass was degraded twice with own isolatedRhizopusoryzae strain in the fermentation process. Next, polymerization process was performed to produce PLA. Polylactic acid obtained was analyzed via Fourier transform infrared (FTIR) and differential scanning calorimetry (DSC). From the FTIR analysis, it can be seen that PLA was successfully produced from kenaf biomass especially at 1,741.42 cm-1 and the band around the region of 1,650-1,450 cm-1when compared to the commercial PLA. In terms of thermal properties, the glass transition temperature (Tg) of PLA from kenaf biomass was around 74.83oC, with its melting temperature (Tm) was in the range of 122 to 125oC, whereas its crystallization temperature (Tc) was not clearly observed. Low molecular weight (444 to 543 g/mol) and low polydispersity index (PD) (1.2) of PLA produced from kenaf biomass by gel permeation chromatography (GPC) analysis indicated that the polymer hasa poor stability state.